PENDIDIKAN SEKS BAGI ANAK USIA DINI: LANGKAH ANTISIPASIF DAN SOLUTIF TERHADAP PELECEHAN SEKS ANAK - Helbert Igilemba Ondja; Melyarmes Hodner Kuanine (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2022)
Sex education is very important to be taught at an early age. Considering the phenomena that occur in society, especially at an early age, related to sex which is considered taboo and inappropriate to talk about and the impact of sin which causes humans not to view sex as a gift from God. This article will describe the idea of the importance of sex education for early childhood. The method used in this paper is a descriptive qualitative approach using a literature study. The author analyzes various literatures related to the discussion of sex education, then formulates the theological relevance for the importance of early sex education. The results of this study illustrate that parents, churches and educational institutions must provide guidance with a theological approach through dynamic Bible teaching. Sex education should be considered as part of the learning process to support personality development. Parents have an important role to prevent deviant sexual behavior by teaching sex education directly and continuously to children as early as possible in the family according to Bible values so that at an early age they get the right picture and accept that their sexuality is an integral part of their lives. responsibly.